1952
DOI: 10.1677/joe.0.0080148
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Neurohypophysis in the Milk-Ejection Reflex

Abstract: Nursing and suckling behaviour of rabbits is described, and evidence given that an active process of milk ejection ('let-down') occurs in this as in other species.Intravenous injection of posterior pituitary extracts in anaesthetized rabbits resulted in ejection of milk from a cannulated teat duct. The threshold dose was about 5 mU. and maximal responses were produced by 200 mU. of extract. Whole posterior pituitary extract was more effective than the oxytocic fraction, which was in turn more effective than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1

Year Published

1959
1959
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(47 citation statements)
references
References 3 publications
(3 reference statements)
5
41
1
Order By: Relevance
“…The finding that a comparatively small amount of milk was obtained only in lesioned rats when replacement therapy with oxytocin was performed, agreed with the findings of Cross and Harris(1952)in the S. O. H. tract lesioned rabbits and with those of McCann et al (1958)in the S. O. H. lesioned rats. It may be possible to ascribe this diminution of the milk yield to the partial impairment of the anterior pituitary gland as McCann et al suggested.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding that a comparatively small amount of milk was obtained only in lesioned rats when replacement therapy with oxytocin was performed, agreed with the findings of Cross and Harris(1952)in the S. O. H. tract lesioned rabbits and with those of McCann et al (1958)in the S. O. H. lesioned rats. It may be possible to ascribe this diminution of the milk yield to the partial impairment of the anterior pituitary gland as McCann et al suggested.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, evidence has been found which suggests a relationship between the ventromedial nucleus or S. O. H. tract and the posterior lobe of the pituitary, due to the mechanism of oxytocin secretion (Harris, 1955;Cross and Harris, 1952;Shimizu et al , 1956Shimizu et al , , 1959Ban et al , 1958;Yokoyama, 1956;Fujii, 1957;McCann et al , 1959):therefore, it appears reasonable to believe that the lesions of the present experiment blocked only the secretory mechanism of the oxytocic hormone, while the secretory mechanism of the anterior pituitary hormone was spared. If this explanation were to be correct, the lactational activity of the mammary glands of lesioned rats could be maintained by the removal of the accumulated milk through the injection of oxytocin(the importance of the removal of engorgement in maintaining the secretory activity of the mammary glands was suggested by Cowie, 1957;Mizuno and Chikamune, 1958;Yokoyama and Ota, 1959), since the secretion of the galactopoietic hormone resulting from the suckling stimuli remains intact.…”
Section: Discussionmentioning
confidence: 99%
“…Several indices based on litter growth (Daggs, 1935;Brody & Nisbet, 1938;Cowie & Folley, 1947;Schultze, 1954) (Uyldert, 1946 (Bruce, 1958 On the assumption that the weight increase of young rats, entirely dependent on their mother's milk, represents about 50 to 60% of the milk yield (Brody & Nisbet, 1938;Cowie & Folley, 1947;Cross & Harris, 1952), these females weighing about 320 g produced from 4 to 6 kg milk each during a single lacta¬ tion with no stimulation other than vigorous suckling (Table 2). …”
Section: Fosteringmentioning
confidence: 99%
“…Although milk secretion can be induced in mammary-gland transplants devoid of nervous connections (Strieker, 1929), the availability of the milk present in the gland when the young start to feed depends on the proper functioning of the milk-ejection reflex (Cross & Harris, 1952). The continued secretion of milk demands appropriate hormonal conditions which are main¬ tained by suckling (Selye, 1934;Folley, 1956), and when the young are weaned the withdrawal of the suckling stimulus, rather than the accumulation of milk within the gland, is primarily responsible for the rapid involution that takes place at that time (Selye, 1934;Williams, 1945).…”
Section: Introductionmentioning
confidence: 99%
“…He had concluded (Harris 1948a) that direct electrical stimulation was ineffective in triggering secretion from the anterior pituitary, but the posterior pituitary was innervated by a nervous tract -the supraoptico-hypophysial tract. Cross & Harris (1950, 1952 showed that the electrical stimulation of this tract caused an increase in intramammary pressure in lactating rabbits, which suggested that the pituitary contains a releasable factor that can induce milk let-down. Harris et al (1969) later showed that the mammary response depended strongly on the stimulus frequency -only at frequencies in excess of 40 Hz was there an appreciable response -a finding that would prove to be prescient ( Fig.…”
Section: Introductionmentioning
confidence: 99%